2023
DOI: 10.3390/coatings13030641
|View full text |Cite
|
Sign up to set email alerts
|

Water-Free SbOx ALD Process for Coating Bi2Te3 Particles

Abstract: We developed a water-free atomic layer deposition (ALD) process to homogeneously deposit SbOx using SbCl5 and Sb-Ethoxide as precursors, and report it here for the first time. The coating is applied on Bi2Te3 particles synthesized via the solvothermal route to enhance the thermoelectric properties (i.e., Seebeck coefficient, thermal and electrical conductivity) via interface engineering. The amorphous character of the coating was shown by the missing reflexes on the X-ray diffractograms (XRD). A shift from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We also reported that the formation of the heterointerfaces in Bi 2 Te 3 -based alloys through ALD could reduce the resistivity by the interfacial doping, 35,36 and κ L by enhancement of phonon scattering at the heterointerfaces. 23,31,37 Consequently, the combination of the porous BST with interface engineering using ALD may yield synergistic effects in terms of decreased resistivity and κ L and enhanced mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported that the formation of the heterointerfaces in Bi 2 Te 3 -based alloys through ALD could reduce the resistivity by the interfacial doping, 35,36 and κ L by enhancement of phonon scattering at the heterointerfaces. 23,31,37 Consequently, the combination of the porous BST with interface engineering using ALD may yield synergistic effects in terms of decreased resistivity and κ L and enhanced mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…ALD, which is a thin-film growth technique based on a self-limiting mechanism, enables the conformal coating of heterogeneous thin films over thermoelectric powders. Thus, the introduction of the ALD technique allows for the creation of a core–shell structure consisting of a thermoelectric core and a heterointerface. In particular, the use of the ALD approach for fabricating Bi 2 Te 3 -based alloys has been reported to result in grain refinement, , indicating the possibility of improving the mechanical strength of the materials. Furthermore, the heterointerfaces formed through ALD can further enhance mechanical strength by inhibiting the propagation of cracks and dislocations.…”
Section: Introductionmentioning
confidence: 99%